Marketing Strategy to Increasing of Cycling Apparel Sales (Case on Urbancase) - Aprizal, Doni; Aldianto, Leo (The Indonesian Journal of Business Administration, 2016)
Abstract - Urbancase was established in Bandung city since 2013, this company is clothing apparel specifically to support cycling activities. The first time company producing bags for cycling that has advantage of multifunction bag for cyclist. As a startup company Urbancase encountered several issue which are low distribution, lack of promotion activities and low brand awareness. All these issues affect the sales performance of Urbancase. In Order to solve the issue, the company’s analyzes condition using STP, 4P’s Marketing Mix and Competitor Analysis. After Analyzing the condition of the company, it is found root causes of the problem there is no well planned marketing program and all the activities are still done by the owner alone. To make solving the problem, the company’s describe the 4P's Marketing Mix. Before making development Marketing Mix, first performed STP process in order to marketing program in accordance with the target market. The solutions proposed in this thesis is in the form of new 4P’s Marketing Mix that will attract customers, widen distribution, improve branding, and increase brand awareness. The proposed solution make variety of basic cycling apparel for cyclist, make pricing strategy like a discount price for special moment, member discount and make reseller or wholesale pricing strategy. Make promotion program that is offline promotion such as cooperate with cycling community & bicycle event organizer and organize regular cycling event, online promotion such as promotion by utilizing Google SEO & Google Map, advertise on Facebook, Instagram, Bukalapak.com and make short video as media campaign that became viral on social media, hire marketing employees to increase the number sales and consignment places and hire graphic designer or photographer to create attractive promotion material. All solution are planned to be implemented in 12 months. By implementing all of the solutions, it is expected that after 12 months all the issue that currently encountered by the company will be resolved and the sales performance will improved. Keywords: Fashion Business, Cycling Apparel, Marketing Strategy, Bicycle, Urbancase.